Africa Out of Africa: notes to think Africanism in Colombia - Kalulambi Pongo, Martín (Pontificia Universidad Javeriana, 2014)
From the generic notion of Africanism, understood like the set of "social and human sciences applied to Africa", the author makes a balance on the African studies in Colombia, especially in anthropology and history. He sustains that African studies do not have to loose their specificity before the height of afro Colombian studies. As objectives one sets out: a) To explain the genesis of the different writings of the black Colombias and Africa; b) to discuss the emptiness and the present dilemmas of African studies and c) to indicate the susceptible perspective to position the African studies in the Colombian average where the knowledge take place.